Pharmacological therapy in patients with osteoarthritis and metabolic disorders: focus on diacerein - O.V. Kuryata; M.M. Grechanyk (Bolʹ, Sustavy, Pozvonočnik, 2025)
Background. Osteoarthritis (OA) is the most common age-related degenerative joint disease and a leading cause of pain and disability in the ageing population. The study aimed to analyze current recommendations and literature data on approaches to OA treatment in patients with comorbidities and metabolic disorders, focusing on diacerein. Materials and methods. An analytical review of literature data from 2003 to 2024 was conducted using scientific databases such as PubMed, Web of Science, Scopus, and Google Scholar. The search was performed using key terms “osteoarthritis”, “metabolic disorders”, “comorbidity, “gout”, “hyperuricemia”, “SYSADOA”, “diacerein” and “effectiveness”. Results. OA frequently coexists with metabolic diseases and other pathologies that accelerate OA progression, significantly worsen physical function impairment, and increase mortality in OA patients. Current research examined the relationship between OA and other diseases, considering age, gender, obesity, hyperuricemia, and gouty arthritis (GA). Comorbidity of OA with GA affects the clinical picture of both diseases, worsens patients’ quality of life, and therefore requires a personalized approach to pharmacotherapy selection. Symptomatic slow-acting drugs for osteoarthritis (SYSADOA) are gaining increasing importance in OA treatment, but various medical associations have differing views on their clinical and economic justification. Future research may focus on differentiating their use based on the affected joint area, as reflected in ESCEO recommendations, or on personalized approaches tailored to specific phenotypes and comorbidities (OARSI recommendations). Conclusions. In our opinion, the combination of OA with hyperuricemia and gout remains underestimated in current recommendations, particularly regarding treatment approaches that consider the inflammatory induction characteristics of this comorbidity. One potentially promising option among SYSADOA drugs in these conditions is diacerein, given its specific effects and safety profile.